Nenaravne nenesreče - Komac, Blaž (Geografski vestnik, 2024)
This article critically examines the concept of natural disaster and sheds light on the epistemological andterminological issues related to its understanding. Natural disasters are not just natural phenomena orrandom accidents, as society plays an important role in their occurrence and consequences. The discus-sion highlights the influence of language on our perception of reality, which shapes our actions, and pointsout that terms such as natural disaster simplify the understanding of the complex relationships betweennatural and social factors. This leads to solutions that focus on dealing with the consequences rather thanrecognizing and tackling the root causes. The author argues for rethinking terminology in order to approachnatural disasters in a more holistic and responsible way.
Keywords: anthropocene; Antropocen; Epistemologija; epistemology; Geografija; geography; Naravne nesreče; natural disasters